PENGARUH DIMETIL SULFOKSIDA (DMSO) DAN SUHU PRESERVASI BERBEDA TERHADAP BAKTERI Methicillin-Resistant Staphylococcus aureus (MRSA) - Kurniawan Kurniawan (IKesT Muhammadiyah Palembang, 2023)
Introduction: S. aureus bacteria are bacteria that cause nosocomial infections in hospitals and that easily develop resistance to antibiotics, forming new strains such as MRSA bacteria that are resistant to the class of antibiotics methicillin (β-lactams). MRSA bacteria are pathogenic and carry a significant proportion of hazards, so it is necessary to maintain and store pure cultures of MRSA bacteria in the laboratory for the purposes of exploration and efforts to control and treat infectious diseases caused by these bacteria. One of the solutions used in bacterial preservation is dimethyl sulfoxide (DMSO) solution, which is universally used. This study aimed to determine the effect of DMSO solution and different temperatures on the preservation of MRSA bacteria. Methods: This study was a quantitative study using multivariate ANOVA test analysis conducted at the Microbiology and Biochemistry Laboratory, Biology Education Study Program, Teaching and Education Faculty (FKIP), Muhammadiyah University, Purwokerto, from July 2022 to October 2022. Results: DMSO solution concentration and temperature Different preservatives can affect the viability of MRSA bacteria, while the best temperature for preserving MRSA bacteria is between 4 oC and 20-28 oC with a significance value (p=0.048). Discussion: The research results show that the concentration of DMSO solution and different preservation temperatures can affect the viability of MRSA bacteria. The best temperature preservation was obtained at 4 oC. Keywords: Bacterial preservation, DMSO, MRSA, Temperature